Impact of timing and dosing of four‐factor prothrombin complex concentrate administration on outcomes in warfarin‐associated intracranial hemorrhage. Issue 5 (28th April 2022) - Cicci, Corey D.; Weiss, Ashley; Dang, Cathyyen; Stanton, Matthew; Feldman, Ryan
Abstract: Study objective: The objective of this study was to evaluate clinical outcomes associated with time to administration and dose of four‐factor prothrombin complex concentrate (4F‐PCC) in patients with ICH on warfarin. Design: This was a single‐center retrospective analysis of patients with ICH on warfarin who received 4F‐PCC. Setting: The site of the study was a large, Level I trauma, academic medical center with a dedicated neurologic intensive care unit and an emergency department (ED) that has approximately 72, 000 visits annually. Patients: Patients were included if they were ≥18 years of age, diagnosed with ICH, had an INR >1 due to warfarin use, and received both 4F‐PCC and IV vitamin K for anticoagulation reversal. Exclusion criteria included patients who were less than 18 years of age, were not currently taking warfarin, had a bleeding site other than ICH, were pregnant or incarcerated, had an inadequate medical record, had a left ventricular assist device, had known liver disease with Child‐Pugh Class C, received anticoagulation with heparin therapy within 24 h of anticoagulation reversal, or did not receive vitamin K within 24 h of hospital admission. Intervention: Our primary outcome was a composite of hematoma expansion or death due to neurologic injury. Treatment groups were defined as receipt of 4F‐PCC within 0–30, 31–60, 61–90, 91–120 min, or greater than 120 min. Hematoma expansion was defined as any increase in hematoma size as assessed by a radiologist via standard 6‐h CT. Death due to neurologic injury was defined as death prior to a repeat CT being performed or documentation of a neurologic cause of death. Adequate INR reversal (INR ≤1.3 on repeat INR) vs. inadequate INR reversal and weight‐based vs. fixed‐dose 4F‐PCC were also assessed. Measurements and Main Results: A total of 94 patients met the inclusion criteria. Forty‐one patients (43.6%) met the composite endpoint, including 60% of the 31–60 min group, 47.6% of the 61–90 min group, 71.4% of the 91–120 min group, and 30.6% of the >120‐min group. A significant difference in primary outcome occurred between the 91–120 min and >120‐min groups (71.4% vs. 30.6%; p = 0.005), but this difference was not observed when accounting for disparities in Glasgow Coma Scale (GCS). Patients with adequate INR reversal were less likely to meet the primary endpoint than those with inadequate INR reversal (28.1% vs. 58.6%; p = 0.0059). There was less failure of anticoagulation reversal with weight‐based dosing compared with fixed dosing (24.2% vs. 65.0%; p < 0.001). Conclusions: No difference in clinical outcomes among 4F‐PCC dosing strategies or time windows to administration was observed in patients with GCS <15. Rates of repeat INR ≤1.3 were higher with weight‐based dosing, suggesting investigation of populations in which fixed dosing may be inappropriate is warranted.